Risk Safety Management in Construction of Metro Rail Projects - V.Nandhini, S.Dhinu Priya, G. Poovizhi, S. Manoj, D.Ambika, V.Santha Rubini (International Journal of Advanced Science and Technology, 2020)
Metro projects are extremely-uncertain for the reason that of the natural uncertainties in-ground and groundwater conditions, multiple construction methods and tools. A lot of attempts made to execute risk safety management systems into urban metro rail construction projects. The aim is to construct a new type of model for risk safety management in metro rail projects, to study the existing risk safety management system and to identify the risks that occur during construction and to create, implement, and determine the efficiency of the model for safety in the construction of metro rail projects. The factors were identified from the literature study. The questionnaire survey has been framed with the nine risk factors and conducted among the employees working in metro tunnel construction projects, and analysis has been carried out through SPSS software. Keywords: Construction risk, Metro, Projects, Safety management